ENHANCING MANUSCRIPT QUALITY: COMMON MISTAKES AND BEST PRACTICES FOR EDUCATIONAL RESEARCH PAPERS - Kornieva, Zoia; Lukianenko, Valentyna; Baklazhenko, Yuliia (Advanced Education, 2024)
This editorial offers a comprehensive guide for researchers planning to publish in high-impact education journals. It identifies common pitfalls in manuscript submissions and provides practical recommendations to overcome them. The paper emphasizes the importance of aligning with a journal’s aims and scope, adhering to submission guidelines, and effectively structuring the manuscript using the IMRAD model. It also addresses weaknesses in various manuscript sections and underlines the significance of citing up-to-date sources, detailed methodological descriptions, ethical considerations, and a logical flow between sections. It concludes that respectful communication in response letters to reviewers significantly impacts the publication decision. Additionally, it offers valuable strategies to improve publication success in high-impact education journals.